The case for ‘fluid’ hierarchies in therapeutic communities - Clarke, Jenelle M. (Emerald, 2017)
Purpose: Democratic therapeutic communities, use a ‘flattened hierarchy’ model whereby staff and clients are considered to have an equal voice, sharing administrative and some therapeutic responsibility. Using the sociological framework of interaction ritual chain theory, this paper explains how TC client members negotiated and enforced community expectations through an analysis of power within everyday interactions outside of structured therapy.